The Impact of the Family Values Crisis on Children’s Right to Education: An Islamic Legal Principles Perspective in Addressing the Challenges of the Modern Era - Muhammad, Syafik; Laili, Fi’liatul; Ashlakha, Hilma Nur; Meidina, Ahmad Rezy (Jurnal Syariah dan Hukum Komparatif, 2025)
The crisis of values within the family has become one of the primary challenges in fulfilling children's educational rights, particularly in shaping the character of early childhood in the midst of modernization, globalization, and technological advancement. This article aims to analyze the impact of the family values crisis on children's right to education and to examine the solutions offered by Islamic legal principles in addressing this phenomenon. This study employs a library research method, drawing on various sources such as books and relevant journal articles. The findings reveal that the family values crisis significantly affects the fulfillment of children's educational rights, especially in terms of moral and spiritual development. Islamic legal principles (fiqh al-munakahat) provide comprehensive guidance for building a strong family structure through the concepts of parental responsibility, moral education, and value-based upbringing grounded in Qur’anic teachings. This article recommends strengthening the role of the family as the primary center of education, underpinned by robust Islamic legal principles, as a solution to the challenges posed by the modern era.